Meanings and functions of discourse particle suda in Papuan Malay - Izak Morin; Wigati Yektiningtyas (Penerbit Universiti Kebangsaan Malaysia, 2025)
Discourse particle suda in Papuan Malay (PM) – a hybrid language spoken in Tanah Papua, Indonesia – plays an important role in natural conversations and written exchanges among the speakers. It becomes evident in utterances or sentences from various stories written by named and unnamed authors in blogs and websites and mobilized by the internet for readers. However, there has not been a study on this particle and therefore this study is to investigate its meanings and functions in utterances or sentences in PM. The content analysis, semantic, and pragmatic methods are used to explore the meanings and functions of this particle in twenty-five utterances or sentences in which it occurs. The results show that the particle suda is not inflected grammatically. It is not a clitic particle so its form does not change regardless of where it appears in an utterance or a sentence. It is both a final-ending type and an initial type. Semantically, it carries more than one meaning. It can have one meaning in one context but entirely different meaning in another context. Pragmatically, it conveys more than one function, but, it cannot serve as one-word answer to a question. The findings can be used by future researchers as a guideline, specifically its methodology, for exploring other discourse particles of PM awaiting to investigate. They can also contribute to the scholarship of discourse particles.